Reprogramming of sorghum proteome in response to sugarcane aphid infestation. (July 2022) - Grover, Sajjan; Cardona, Juan Betancurt; Zogli, Prince; Alvarez, Sophie; Naldrett, Michael J.; Sattler, Scott E.; Louis, Joe
Abstract: Sugarcane aphid (SCA; Melanaphis sacchari Zehntner) is a key piercing-sucking pest of sorghum ( Sorghum bicolor ) that cause significant yield losses. While feeding on host plants, complex signaling networks are invoked from recognition of insect attack to induction of plant defenses. Consequently, these signaling networks lead to the production of insecticidal compounds or limited access of nutrients to insects. Previously, several studies were published on the transcriptomics analysis of sorghum in response to SCA infestation, but no information is available on the physiological changes of sorghum at the proteome level. We used the SCA resistant sorghum genotype SC265 for the global proteomics analysis after 1 and 7 days of SCA infestation using the TMT-plex technique. Peptides matching a total of 4211 proteins were identified and 158 proteins were differentially expressed at day 1 and 7. Overall, proteome profiling of SC265 after SCA infestation at days 1 and 7 revealed the suppression of plant defense-related proteins and upregulation of plant defense and signaling-related proteins, respectively. The plant defense responses based on proteome data were validated using electrical penetration graph (EPG) technique to observe changes in aphid feeding. Feeding behavior analyses revealed that SCA spent significantly longer time in phloem phase on SCA infested plants for day 1 and lesser time in day 7 SCA infested sorghum plants, compared to their respective control plants. Overall, our study provides insights into underlying mechanisms that contribute to sorghum resistance to SCA. Highlights: Sugarcane aphid (SCA) feeding remodels sorghum proteome at early and late stages of aphid feeding. SCA successfully suppressed several plant defense proteins at early stages of aphid herbivory. However, SCA-resistant sorghum plants elevated defense proteins at later stages of SCA feeding. Feeding behavior analysis confirmed that SCA fed better on sorghum plants with low defense status.